Simmons, Betty. New Perlican Photograph of five boys, one on a bike. - Barrett, Terra
A photograph of Jim Callahan riding a bike, Johnny Pearce, Billy Seward, Calvin Peddle and Grenfell Warren standing on either side. A wriggle fence and house can be seen in the background.